The Influence of Transactional Leadership and Entrepreneurial Competence of School Principals on the Effectiveness of Education Financing - Rica Arisanti; Edi Harapan; Pahlawan Pahlawan (International Journal of Educational Research, 2025)
This research examines the influence of transactional leadership and the entrepreneurial competence of school principals on the effectiveness of education financing in primary and secondary education settings. Effective education financing is essential to ensure that limited resources are allocated optimally to improve learning quality, infrastructure, and institutional sustainability. Transactional leadership—marked by clear performance standards, reward and punishment mechanisms, and strict supervision—provides a structured framework for financial accountability and goal achievement. Entrepreneurial competence, on the other hand, equips principals with the ability to recognize funding opportunities, innovate in revenue generation, and manage financial risks. The study adopts a quantitative survey design involving school principals and financial management personnel from a representative sample of public and private schools. Data were collected using validated questionnaires and analyzed through multiple regression to measure the direct and combined effects of the two independent variables on education financing effectiveness. The findings reveal that both transactional leadership and entrepreneurial competence significantly and positively affect financial effectiveness. Transactional leadership strengthens transparency and budget discipline, while entrepreneurial competence fosters diversification of funding sources and innovative financial strategies. These results highlight the strategic importance of integrating leadership development with entrepreneurial training for school principals. Strengthening these competencies not only enhances financial planning and accountability but also reduces dependence on a single funding source, supporting long-term educational sustainability. Future studies are encouraged to explore additional mediating factors such as organizational culture, technological infrastructure, and community involvement to provide a more comprehensive understanding of education financing dynamics.